AN EMPIRICAL METHOD FOR THE DETERMINATION OF SINGLE ION HYDROGEN ISOTOPE SALT EFFECTS IN AQUEOUS ELECTROLYTE SOLUTIONS - Driesner T.; Seward T.M. (My University, 1999)
An empirical method is presented that allows the determination of the individual contributions of anions and cations to the effect of dissolved salts on hydrogen isotope fractionation in aqueous systems (isotope salt effect). The method is solely based on experimental data and does not involve the choice of arbitrary reference values or theoretical assumptions. Plotting experimental liquid-vapor D/H fractionation factors for aqueous solutions of sodium salts vs. O-D stretching frequencies of water molecules in the hydration shells of the anions shows an excellent linear correlation. The distance between this line and the pure water liquid-vapor fractionation data point in the same plot gives the cation contribution to the isotope salt effects. The anion contribution can then simply be derived as the difference between the total salt effect and the cation salt effect. The validity of the concept is demonstrated using precise literature data for the O-D stretching frequencies in the hydration shells of individual ions at 20°C [Bergstrom, P.A., 1991. Single ion hydration properties in aqueous solution: a quantitative infrared spectroscopic study. PhD Thesis. Uppsala University] and for the liquid-vapor hydrogen isotope fractionation between aqueous solutions and water vapor at the same temperature [Stewart, M.K., Friedman, I., 1975. Deuterium fractionation between aqueous salt solutions and water vapor. Journal of Geophysical Research 80, 3812-3818]. Within the limits of experimental uncertainties, the data set shows internal consistency. Cation salt effects, 1000 ln Γ at 20°C, are (in per mil per mole per liter, using the convention of Horita et al. [Horita, J., Cole, D.R., Wesolowski, D.J., 1993a. The activity-composition relationship of oxygen and hydrogen isotopes in aqueous salt solutions: II. Vapor-liquid water equilibration of mixed salt solutions from 50-100°C. Geochimica et Cosmochimica Acta 57, 4703-4711]): Na++0.7; K++0.7; Mg2++6.5; Ca2++1.8; Al3++12. The salt effect of H+ cannot be determined unequivocally. The combined effect of the fractionation of H+ itself plus its salt effect is +4.9. Anion effects are +1.4 for Cl-, +2.7 for Br-, +3.5 for I- and -1.4 for SO42-. Further single anion salt effects are being predicted as -1.8 for F-, +4.9 for NO3-, +6.9 for ClO4- and +5.4 for the triflate ion (CF3SO3-).
Keywords: STABLE ISOTOPES; WATER; SALT EFFECT; INFRARED SPECTROSCOPY